Pyroptosis for osteoarthritis treatment: insights into cellular and molecular interactions inflammatory - Lin, Minghui; Zhang, Cunxin; Li, Haiming; Li, Kang; Gou, Shuao; He, Xiao; Lv, Chaoliang; Gao, Kai (Frontiers in Immunology, 2025)
Osteoarthritis (OA) is a widely prevalent chronic degenerative disease often associated with significant pain and disability. It is characterized by the deterioration of cartilage and the extracellular matrix (ECM), synovial inflammation, and subchondral bone remodeling. Recent studies have highlighted pyroptosis—a form of programmed cell death triggered by the inflammasome—as a key factor in sustaining chronic inflammation. Central to this process are the inflammatory cytokines interleukin-1β (IL-1β) and interleukin-18 (IL-18), which play crucial roles mediating intra-articular pyroptosis through the NOD-like receptor protein 3 (NLRP3) inflammasome. This paper investigates the role of the pyroptosis pathway in perpetuating chronic inflammatory diseases and its linkage with OA. Furthermore, it explores the mechanisms of pyroptosis, mediated by nuclear factor κB (NF-κB), the purinergic receptor P2X ligand-gated ion channel 7 (P2X7R), adenosine monophosphate (AMP)-activated protein kinase (AMPK), and hypoxia-inducible factor-1α (HIF-1α). Additionally, it examines the interactions among various cellular components in the context of OA. These insights indicate that targeting the regulation of pyroptosis presents a promising therapeutic approach for the prevention and treatment of OA, offering valuable theoretical perspectives for its effective management.